A Review of Important Activities and Studies 1969-70 - Planning Commission (Planning Commission, 1970)
The Fourth Five Year Plan (1969-74) Draft was presented to the National Development Council at its meeting held on April 19-20, 1969. While approving the Draft Plan the National Development Council directed the Planning Commission to make a further assessment of the States’ resources after the award of the Fifth Finance Commission had been received. It also directed that the debt position of the States vis-a-vis the Centre be reviewed. Thereafter, the Draft Plan was presented to both the Houses of Parliament. The Fourth Plan Draft was discussed in Lok Sabha on 8th, 9th and 12th May and in Rajya Sabha from 13th May to 15th May, 1969. After its consideration in both the Houses it was discussed on October 31, 1969 first by Prime Minister’s Committee of Members of Parliament on Planning and then by the Consultative Committee of Members of Parliament for Planning Commission.
Government of India Planning Commission